Temperamento de cordeiros da raça crioula em confinamento individual - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Nowadays there is a greater concern by consumers with the origin of the products they consume. And among the points of interest of users, we can highlight the commitment to healthy habits, the quality of sold meat and the growing concern for animal welfare. This is consolidated with the search for information about the origin of marketed meat which relates to its means of production. Producers and industry seek to maintain quality standards, which are associated with animal welfare in order meet the requirements current consumer market. This study aims to describe the temperament of lambs of the Creole breed in individual feedlot system. The experiment was carried out between the months of March to June 2016 in the Ovine Sector of the Federal University of Pampa. Twenty-nine castrated Creole lambs were used. The animals were kept in individual stalls with approximately 1.0 m² each for 90 days, with the first 14 days for adaptation to diet and facilities. Feeding management was carried out twice a day by the same people, in order to characterize a positive human-animal relationship. The assessment of the lambs temperament was held in three stages (beginning, middle and end) of the trial period. The evaluation was made by assigning the composite score (CS), type of march (TM) arena test and measurements of physiological parameters such as heart rate, respiratory rate and body temperature. The results obtained for the physiological parameters were significant, showing the importance of positive human-animal relationship when contact them repeatedly. For the arena test, composite score and type of march there was no statistical difference, however it can be seen that in the course of ratings reactivity decreased. Temperament of Wool Creole, kept in individual feedlot system, did not change with the course of the evaluations, however it is noteworthy that they showed a tendency to decrease the reactivity over the evaluations with frequent and positive contact between humans and animals.
Keywords: Autóctone; Bem estar animal; Ovinocultura; Animal welfare; Autochthonus; Sheep industry; CNPQ::CIENCIAS AGRARIAS